Pemanfaatan Sampah Plastik sebagai Material Paving Block - Ruth Clarissa Tambunan; Julia Saputri (Lembaga Pengembangan Kinerja Dosen, 2024)
As people's consumption levels increase, the plastic waste produced will also increase. It's normal if in the future it becomes a serious environmental problem. We need a technology that is able to replace plastic waste into products that have a long life so that they do not return to waste in a short time. Making paving block products from plastic waste is another way of utilizing plastic waste over a long period of time, in order to increase utilization efficiency and reduce the environmental burden on plastic waste and form innovative products into building materials. The most important problem with plastic is plastic waste which cannot be decomposed naturally. Cleaning up plastic waste takes a very long time, and also the use of plastic can hardly be regulated. Based on the results of surveys, interviews and observations conducted on the community around Kuala Village, the community's awareness of waste processing is very minimal and there are lots of piles of plastic waste which can have a negative impact on health and disrupt the preservation of environmental functions, including residential environments, forests, rice fields, and rivers. To reduce the volume of plastic waste that is not managed properly, efforts are being made to utilize plastic waste to make paving blocks in Kuala Lemang Village. to explore the potential for using plastic waste as an alternative material in making environmentally friendly and sustainable paving blocks. Plastic waste collected from the surrounding environment is processed into mixed materials in making paving blocks. This process involves chopping, mixing with conventional materials such as sand, and testing the strength of the final product. Public acceptance of plastic-based paving blocks has proven positive, especially after trials in the local environment. This research contributes to better plastic waste management and offers new economic opportunities in the construction sector, while supporting sustainable development.